2014
DOI: 10.1371/journal.pone.0097832
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Inequalities in the Prevalence of Multi-Morbidity among the Rural Elderly in Bargarh District of Odisha (India)

Abstract: BackgroundMulti-morbidity among elderly is increasingly recognized as a major public health challenge in most of the developing countries. However, information on the size of population suffering from multi-morbidity and socio-economic differentials of multi-morbidity is scarce. The objectives of this paper are twofold; first, to assess the prevalence of various chronic conditions and morbidity among rural elderly and second, to examine the socio-economic and demographic factors that have a significant effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
96
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(116 citation statements)
references
References 38 publications
17
96
2
1
Order By: Relevance
“…15 The higher likelihood of multimorbidity among older adults, women, and those with higher income level is congruent with findings from studies from South Asia. 4,6 The observed inverse correlation between socioeconomic status and multimorbidity, though, contrasts with that of Western countries, but it is consistent with previous findings from India. …”
supporting
confidence: 90%
See 1 more Smart Citation
“…15 The higher likelihood of multimorbidity among older adults, women, and those with higher income level is congruent with findings from studies from South Asia. 4,6 The observed inverse correlation between socioeconomic status and multimorbidity, though, contrasts with that of Western countries, but it is consistent with previous findings from India. …”
supporting
confidence: 90%
“…[1][2][3] In the developing countries, little information on multimorbidity is available and is based on secondary data and limited to a only a few chronic conditions and geriatric groups. [4][5][6] With our previous study, for which data were based on the World Health Organization (WHO) Study on Global Aging and Adult Health (SAGE), we reported a 8.9% prevalence of multimorbidity in Indian adults. 7 Our systematic review on multimorbidity in South Asia found a lack of uniformity in the definition and assessment of multimorbidity, and no information from primary care in India.…”
Section: Introductionmentioning
confidence: 95%
“…Investigations into the existence of simultaneity, without attributing difference to the accumulation of diseases, found similar results in the elderly. 23 This fact may be justified by the transition of marital status from single to living with partners and adopting unhealthy behaviors, such as reduction in physical activities, poorer diet and sleeping patterns. 24 There was no distinction between the prevalence of black/brown and white ethnicity/skin color in the population living in the Brazilian state capital cities.…”
Section: Discussionmentioning
confidence: 99%
“…5 Smoking and chewing tobacco increase morbidity both among adults and the elderly. 6,7 Although there is great variation in substance use across different regions of India, 8 limited efforts have been made to understand the prevalence and determinants of substance use at the regional level. In particular, there is a dearth of research on substance consumption in Northeast India (NEI).…”
Section: Introductionmentioning
confidence: 99%